An iRGD‐conjugated photothermal therapy‐responsive gold nanoparticle system carrying siCDK7 induces necroptosis and immunotherapeutic responses in lung adenocarcinoma - Rui Cai; Meng Wang; Meiyuan Liu; Xiongjie Zhu; Longbao Feng; Zhongjian Yu; Xia Yang; Zhiwu Zhang; Huili Guo; Rui Guo; Yanfang Zheng (Wiley, 2023)
Abstract Although immunotherapy has improved the clinical treatment of lung adenocarcinoma (LUAD), many tumors have poor responses to immunotherapy. In this study, we confirmed that high expression of Cyclin‐Dependent Kinase 7 (CDK7) promoted an immunosuppressive macrophage phenotype and macrophage infiltration in LUAD. Thus, we have developed an internalizing‐RGD (iRGD)‐conjugated gold nanoparticle (AuNP) system which carries siCDK7 to activate the antitumor immune response. The iRGD‐conjugated AuNP/siCDK7 system exhibited good tumor targeting performance and photothermal effects. The AuNP/siCDK7 system with excellent biosafety exerted a significant photothermal antitumor effect by inducing tumor cell necroptosis. Furthermore, the AuNP/siCDK7 system ameliorated the immunosuppressive microenvironment and enhanced the efficacy of anti‐PD‐1 treatment by increasing CD8+ T cell infiltration and decreasing M2 macrophage infiltration. Hence, this iRGD‐conjugated AuNP/siCDK7 system is a potential treatment strategy for lung adenocarcinoma, which exerts its effects by triggering tumor cell necroptosis and immunotherapeutic responses.